EFEKTIVITAS PSIKOEDUKASI DUKUNGAN SOSIAL TERHADAP TINGKAT STRES PEGAWAI BEA CUKAI GRESIK DALAM MENGHADAPI MUTASI KERJA - Rifqi Pratama Putra; Setyani Alfinuha (Universitas Muhammadiyah Gresik, 2024)
Background: Customs employees are faced with various unique and complex challenges, especially regulations that require employees to undergo regular job transfers which can trigger stress. So far there has been no special psychological support program provided for employees who will transfer jobs. Various studies show that social support has an effective effect on stress. Objective: This research seeks to reveal the effectiveness of social support psychoeducation to reduce the stress level of employees undergoing job transfers. Method: This research uses a quasi-experiment design with a non-randomized one group pre-test post-test design. The number of participants in this research was 15 employees consisting of Gresik Customs and Excise who were aged between 22 - 30 years and were about to undergo a job transfer. Stress levels were measured using the Perceived Stress Scale and analyzed using the paired sample t-test. Results: Research shows that social support psychoeducation is effective in reducing the stress level of employees undergoing job transfers. Conclusion: Social support psychoeducation has proven to be effective in reducing stress levels. Social support psychoeducation helps employees understand and identify the various sources of social support they have, thereby helping them manage stress when changing jobs.